NUTRITION OF PREGNANT AND NURSING WOMEN: USE OF SPECIALIZED NUTRIENTS - M.V. Gmoshinskaya; L.S. Konovalova; E.Yu. Demkina (Вопросы современной педиатрии, 2011)
The article is dedicated to peculiarities of women nutrition during pregnancy and lactation. We present a list of specialized nutrients for nutrition of pregnant and nursing women with various alimentary-dependent pathology. The possibility of use, ingredients and nutritional value are shown on the example of milk formula «Celia Mama». Key words: pregnant women, nursing mothers, specialized nutrients. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 81–87.)